Jejak Religi Pada Makam Gerald Alfred Cup di Perkebunan Kina Cinyiruan Masa Kolonial - Lia Nuralia (Kemendikbud, 2021)
Cinyiruan Plantation of Chinchona has become part of the garden (afdeeling) of the Kertamanah Plantation. Traces of the Cinyiruan Plantation culture can still be traced, one of which is the tomb of Gerald Alfred Cup. What and how the existence of the tomb is the main problem in this paper. The research method used is desk research with a historical approach. The results obtained are that the tomb of Gerald Alfred Cup shows traces of Christian religion in the Cinyiruan Plantation of Chinchona, and the tolerant religious life on the plantations during the colonial period. Traces of religion based on the shape of the tomb marker and European (Dutch) name on tomb inscription. Gerald Alfred Cup or Tuan Keup is a Dutch, plant expert and the last Cinyiruan Plantation of Chinchona of Administrator. The tolerant religious life in the plantations is indicated by the traces of the tomb as an indication of the existence of Christianity and the presence of mosques in the settlements of the workers. The plantation workers are the original indigenous people of the local village who are mostly Muslim.